2020
DOI: 10.21203/rs.3.rs-127434/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Efficacy of OnabotulinumtoxinA Treatment in Patients With Comorbid Migraine and Depression: A Meta-analysis

Abstract: Background: Migraine and depression are highly prevalent and partly overlapping disorders that cause strong limitations in daily life. Patients tend to respond poorly to the therapies available for these diseases. OnabotulinumtoxinA has been proven to be an effective treatment for both migraine and depression. While many studies have addressed the effect of onabotulinumtoxinA in migraine or depression separately, a growing body of evidences suggest benecial effects also for patients comorbid with migraine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Botox has been shown to be more effective in treating migraine and depression co-morbidities. A Meta-analysis (Affatato O, Moulin T C, Pisanu C, et al, 2021) compared the efficacy of Botox in the treatment of migraine or depression versus patients with both disorders, and the results showed that Botox was more effective in the treatment of comorbidities than patients with migraine or depression alone, with significant improvements in depressive symptoms and quality of life, as well as significant improvements in the severity and impact of migraine pain and reduced headache frequency. One difference is that patients with comorbidity based on the BDI scale have a better prognosis for depression than patients with depression alone.…”
Section: Substitution Therapymentioning
confidence: 99%
“…Botox has been shown to be more effective in treating migraine and depression co-morbidities. A Meta-analysis (Affatato O, Moulin T C, Pisanu C, et al, 2021) compared the efficacy of Botox in the treatment of migraine or depression versus patients with both disorders, and the results showed that Botox was more effective in the treatment of comorbidities than patients with migraine or depression alone, with significant improvements in depressive symptoms and quality of life, as well as significant improvements in the severity and impact of migraine pain and reduced headache frequency. One difference is that patients with comorbidity based on the BDI scale have a better prognosis for depression than patients with depression alone.…”
Section: Substitution Therapymentioning
confidence: 99%